VALUE CHAINS AND ILLICIT FINANCIAL FLOWS FROM TRADE MISINVOICING: INDONESIA-SINGAPORE - Rusydi, Mohamad Khoiru; Irianto, Gugus; Achsin, M. (Jurnal Aplikasi Manajemen, 2023)
This study aimed to analyze the potential for illicit financial flows with the practice of misinvoicing the impact of differences in recording the value of exports and imports of Indonesia and Singapore, as well as calculating the potential loss of state revenue from the tax sector of the trade balance disparity in Indonesia and Singapore. This research is a type of quantitative research. The data source is secondary data collected from the Indonesia-Singapore trade balance in 2016-2020 with a sample of 20 leading Indonesian export commodities to Singapore. Data analysis focuses on estimating the size of illicit financial flows and the potential loss of state revenue. The trade misinvoicing scenario is under-invoicing exports and over-invoicing exports. Meanwhile, the focus is on under-invoicing exports for calculating the potential lost state revenue. This study has found that from the 20 commodities traded between Indonesia and Singapore, there was a difference between over-invoicing and under-invoicing of US$.830 million, which means that illicit financial flows from Indonesia to Singapore have reached US$830 million from trade misinvoicing practices from Indonesia 2016 to 2020. Meanwhile, the potential loss of state revenue from the tax sector due to under-invoicing exports in the 5 (year) 2016-2020 period is around US$563 million. This potential loss results from Income Shifting by exporting companies to Singapore.